A study of the influencing factors of mobile social media fatigue behavior based on the grounded theory. Issue 2 (3rd February 2020) - Zhang, Yanfeng; Liu, Yali; Li, Wenzhuo; Peng, Lihui; Yuan, Cong
Abstract : Purpose: This paper aims to discuss major influencing factors causing users' mobile social media fatigue and divides them into three hierarchies, including causal factors, intermediary factors and outcome factors. The study also sorts out connections between different levels of factors, thus providing effective guidance for the sustained development of social media. Design/methodology/approach: Based on the grounded theory and by collecting data through in-depth interviews, the authors use open coding, axial coding and selective coding to analyze major influencing factors of users' mobile social media fatigue, build a model using the software NVivo 11, organize and analyze mobile social media fatigue behavior and identify the relationships by combining the interpretive structural model and explore connections among the factors. Findings: The influencing factors of mobile social media fatigue behavior conform with the stressors-strains-outcomes (SSO) theoretical framework, where stressors (S) include the five factors of fear of missing out, perceived overload, compulsive use, time cost and privacy concerns; strains (S) include the five factors of a low sense of achievement, emotional anxiety, reduced interest, social concerns and emotional exhaustion; outcomes (O) include the six factors of neglect behavior, diving behavior, avoidance behavior, tolerance behavior, withdrawal behavior and substitution behavior. Research limitations/implications: It focuses on the discussion of the interactions between users' stressors, strains and outcomes without fully considering the impact of social environment and educational background on social media fatigue behavior. This study only focuses on one social media platform in the Chinese context, namely, WeChat. We reply on the qualitative research method to construct the relationships between social media fatigue factors because we were mainly interested in how users would respond psychologically and emotionally to social media fatigue behavior. Practical implications: The study has extended the application of the SSO theory. Additionally, the research method and model used in this paper may serve as guidelines to other interested scholars who intend to explore relevant variables and conduct further research on the influencing factors of social media fatigue. In analyzing the causality of social media fatigue, the study has integrated the intermediary factor strain to display users' strains from social media stress with a more detailed path discussion on the causality of social media fatigue, which has not received broad attention in previous research literature on social networking services users' use. Social implications: In this study, text data are collected in a diversity of forms combined, allowing respondents to answer questions without being limited by the questions in the questionnaire, which helped us to identify new variables of social media fatigue. As a result, we were able to dig out the fundamental causes of social media fatigue and potential connections between the factors. Relevant scholars, users and businesses may analyze, manage and forecast users' social media fatigue behavior by analyzing the type of social media stress and users' state, providing guidance for the proposal of corresponding management strategies. Originality/value: Most relevant studies focus on the sustained use of social media, and there is a scarcity of studies on social media fatigue in China. There is very limited research that conducts model analysis of social media fatigue through the integration of stressors, strains and outcomes.